Safety and immunogenicity of the adjunct therapeutic vaccine ID93 + GLA-SE in adults who have completed treatment for tuberculosis: a randomised, double-blind, placebo-controlled, phase 2a trial. Issue 4 (April 2021) - Day, Tracey A; Penn-Nicholson, Adam; Luabeya, Angelique Kany Kany; Fiore-Gartland, Andrew; Du Plessis, Nelita; Loxton, Andre G; Vergara, Julie; Rolf, Tom A; Reid, Tim D; Toefy, Asma; Shenje, Justin; Geldenhuys, Hendrik; et al.
Summary: Background: A therapeutic vaccine that prevents recurrent tuberculosis would be a major advance in the development of shorter treatment regimens. We aimed to assess the safety and immunogenicity of the ID93 + GLA-SE vaccine at various doses and injection schedules in patients with previously treated tuberculosis. Methods: This randomised, double-blind, placebo-controlled, phase 2a trial was conducted at three clinical sites near Cape Town, South Africa. Patients were recruited at local clinics after receiving 4 months of tuberculosis treatment, and screened for eligibility after providing written informed consent. Participants were aged 18–60 years, BCG-vaccinated, HIV-uninfected, and diagnosed with drug-sensitive pulmonary tuberculosis. Eligible patients had completed standard treatment for pulmonary tuberculosis in the past 28 days. Participants were enrolled after completing standard treatment and randomly assigned sequentially to receive vaccine or placebo in three cohorts: 2 μg intramuscular ID93 + 2 μg GLA-SE on days 0 and 56 (cohort 1); 10 μg ID93 + 2 μg GLA-SE on days 0 and 56 (cohort 2); 2 μg ID93 + 5 μg GLA-SE on days 0 and 56 and placebo on day 28 (cohort 3); 2 μg ID93 + 5 μg GLA-SE on days 0, 28, and 56 (cohort 3); or placebo on days 0 and 56 (cohorts 1 and 2), with the placebo group for cohort 3 receiving an additional injection on day 28. Randomisation was in a ratio of 3:1 for ID93 + GLA-SE and saline placebo in cohorts 1 and 2, and in a ratio of 3:3:1 for (2 ×) ID93 + GLA-SE, (3 ×) ID93 + GLA-SE, and placebo in cohort 3. The primary outcomes were safety and immunogenicity (vaccine-specific antibody response and T-cell response). For the safety outcome, participants were observed for 30 min after each injection, injection site reactions and systemic adverse events were monitored until day 84, and serious adverse events and adverse events of special interest were monitored for 6 months after the last injection. Vaccine-specific antibody responses were measured by serum ELISA, and T-cell responses after stimulation with vaccine antigens were measured in cryopreserved peripheral blood mononuclear cells specimens using intracellular cytokine staining followed by flow cytometry. This study is registered with ClinicalTrials.gov, number NCT02465216 . Findings: Between June 17, 2015, and May 30, 2016, we assessed 177 patients for inclusion. 61 eligible patients were randomly assigned to receive: saline placebo (n=5) or (2 ×) 2 μg ID93 + 2 μg GLA-SE (n=15) on days 0 and 56 (cohort 1); saline placebo (n=2) or (2 ×) 10 μg ID93 + 2 μg GLA-SE (n=5) on days 0 and 56 (cohort 2); saline placebo (n=5) on days 0, 28 and 56, or 2 μg ID93 + 5 μg GLA-SE (n=15) on days 0 and 56 and placebo injection on day 28, or (3 ×) 2 μg ID93 + 5 μg GLA-SE (n=14) on days 0, 28, and 56 (cohort 3). ID93 + GLA-SE induced robust and durable antibody responses and specific, polyfunctional CD4 T-cell responses to vaccine antigens. Two injections of the 2 μg ID93 + 5 μg GLA-SE dose induced antigen-specific IgG and CD4 T-cell responses that were significantly higher than those with placebo and persisted for the 6-month study duration. Mild to moderate injection site pain was reported after vaccination across all dose combinations, and induration and erythema in patients given 2 μg ID93 + 5 μg GLA-SE in two or three doses. One participant had grade 3 erythema and induration at the injection site. No vaccine-related serious adverse events were observed. Interpretation: Vaccination with ID93 + GLA-SE was safe and immunogenic for all tested regimens. These data support further evaluation of ID93 + GLA-SE in therapeutic vaccination strategies to improve tuberculosis treatment outcomes. Funding: Wellcome Trust (102028/Z/13/Z).